Veillonella Bacteremia in Alcoholic Hepatitis - Patrick Lee; Brandon K. K. Fields; Tom Liang; Michael P. Dubé; Seth Politano (Case Reports in Hepatology)
Veillonella species are commensal bacteria of the human oral, gut, and vaginal microbiota that are rarely identified as clinically relevant pathogens. Here, we describe a novel case of Veillonella atypica bacteremia in a patient with biopsy-proven alcoholic hepatitis. Veillonella species have been correlated with disease severity and hepatic encephalopathy in liver diseases such as autoimmune hepatitis and cirrhosis. Their abundance has also been recently observed to be increased in alcoholic hepatitis, where postinflammatory infections are known to impact mortality. This case report highlights the possible clinical manifestations that result from significant gut dysbiosis in patients with severe alcoholic hepatitis. Early identification and treatment of Veillonella bacteremia in susceptible populations could be crucial to survival given this organism’s predilection for causing life-threatening infections, including meningitis, endocarditis, and osteomyelitis.